DEVELOPING THE PHYSICAL FITNESS OF PRIMARY SCHOOL STUDENTS THROUGH GYMNASTICS - Rayimova Dilnoza Faxriddin kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the role of gymnastics in developing the physical fitness of primary school students. It outlines the physiological, psychological, and educational benefits of gymnastics-based activities in the early school years. The paper highlights how gymnastics improves strength, flexibility, balance, coordination, motor skills, and overall physical health. Various forms of gymnastics—basic exercises, rhythmic gymnastics, acrobatics, and apparatus-based activities—are explored for their contribution to children’s growth and development.